Evaluation of the half-power bandwidth method to estimate damping in systems without real modes. - Olmos, Bertha A.
The objective of this work was to assess the significance of the values of damping obtained applying the half-power bandwidth method to the frequency response records of the steady-state response of a system that does not possess real modes either because the damping matrix does not satisfy the orthogonality condition or because its parameters are functions of frequency. A multi-degree of freedom system with real modes and different types of damping is considered first. A two degree of freedom system with an arbitrary damping matrix, a rigid mass on an elastic foundation subjected to vertical and coupled horizontal/rocking vibrations, and a single degree of freedom model of a building accounting for inertial soil structure interaction effects are considered next in more detail. The results show that the predictions of the method, when applicable compare very well with those provided by approximate formulae and procedures used in practice.
Keywords: Effective damping; System identification; Half-power bandwidth method